A low-cost home security notification system using IoT and Telegram Bot: A design and implementation / Mohd Nizam Osman ... [et al.] - Osman, Mohd Nizam; Ismail, Muhammad Haika Faeq; Sedek, Khairul Anwar; Othman, Nor Arzami; Maghribi, Mushahadah (UiTM Cawangan Perlis, 2022)
Home security is a critical issue, especially for the civilians to protect their property from harm. Currently, the increase in home breaking usually occurs during school holidays and public holiday seasons. Therefore, to overcome the problem and the main objective is to design and develop a low-cost home security notification system using PIR sensor to detect movement of intruders, Raspberry Pi Camera, GPS module integrated with Raspberry Pi Zero WH to send an alert notification message with image, date, location, and time via Telegram Bot to the house owner’s and people nearby through a smart phone. The system utilizes the System Development Life Cycle (SDLC) by implementing the waterfall model as the methodology. Three experiments were conducted to examine the effectiveness of the system which is sensor detection range, response time and user acceptance test (UAT). The finding indicates that the home security notification system was efficient, effective, low-cost, and easy to use. Besides, the system can detect the presence of the intruder and send the notification message in a reasonable time. Meanwhile, the result from the UAT indicates that the proposed system has a positive impact and to be well accepted by the majority of the users. Hence, the system can help the house owners to take immediate action such as calling the neighbourhood association or police department authority when the system detects an intruder in the house.